تمييز الشخص المدخن اعتماداً على تحليل مثلثات صوتية مُوَلَّدَة (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2017)
تمَّ في هذا البحث اقتراح معيار لدراسة خصائص إشارة الصوت لكل من صنفي المدخنين وغير المدخنين، إذ تمَّ بناء قاعدة بيانات تضم ملفات صوتية تعود إلى 12 شخص سوري (6 أشخاص مدخنين و6 أشخاص غير مدخنين)، تتراوح أعمار جميع الأشخاص بين 35 و45 عام، جميعهم ذكور ويعيشون في مناطق ريفية متجاورة.استغرقت عملية تسجيل الملفات الصوتية ثلاث ساعات، حيث لفظ جميع المتحدثين جملة /أَنَاْ أُحِبُّ سُوْرِيْة /، وهي جملة غنية صوتياً تشمل جميع الأحرف الصوتية الطويلة (الألف والواو والياء) والحروف الصوتية القصيرة (الفتحة والضمة والكسرة).اعتماداً على التسجيلات الناتجة تمَّ توليد المثلثات الصوتية الطويلة والقصيرة، وهي مثلثات هندسية رؤوسها تمثل قيم ترددات توافقيات المجرى الصوتي الممتد من الحبال الصوتية إلى الشفاه وتسمى النغمات ((Formants، حيث تمَّ توليد المثلثات الصوتية الطويلة (AAIIUU) في 10 مستويات، وكذلك المثلثات الصوتية القصيرة (AIU) في 10 مستويات؛ وبذلك نتج 20 مثلث صوتي لكل شخص. تمَّ في كل مستوي حساب المسافة بين جميع مراكز المثلثات الصوتية واختيار المسافة الأدنى (d)، فيكون المستوي ذو القيمة الأعظمية للمسافة (d) هو المستوي الممثل للمثلث الصوتي الأنسب لتمييز المدخنين من غير المدخنين، وقد تحقق ذلك بالنسبة للمثلثين AIU35 و .AAIIUU45 In this research, a new comparison criterion was proposed to study properties of the audio signal for each of the varieties of smokers and non-smoking persons. For this purpose, a database for smokers has been created. The smoker database contains 12 Syrian native speakers, six of them were smokers and the others were non-smokers. The smokers had been smoking for more than 10 years. All speakers were men and their ages ranging between 35 and 42 years old. They live in rural towns and speak the same dialect.Syrian vowels can be classified into long vowels and short ones. The long vowels are /AA/, /UU/, /II/ pronounced as ([ي, و, ا]) and the short vowels are /A/, /U/, /I/ pronounced as ([كسرة, ضمة, فتحة]). In this study, the Speakers have to pronounce the following sentence /I love Syria/ pronounced as ([أَنَاْ أَحَبُّ سُوْرِيْة]), and it was spoken during three hours. This sentence is rich with vowels.For each speaker, a long vowel triangle in ten planes and a short vowel triangle in ten planes as well were generated and analyzed. A new criterion was suggested to determine the most suitable vowel triangle for smoker distinction. This criterion depends on calculating the different distances among all centers of vowel triangles in each plane and determining the minimal distance called d. For each plane, the most suitable vowel triangle had been set as AIU35 short vowel triangle and AAIIUU45 long vowel triangle.